PENEGAKAN HUKUM BAGI ANGGOTA KEPOLISIAN NEGARA REPUBLIK INDONESIA PELAKU TINDAK PIDANA NARKOTIKA YANG DITUNTUT PIDANA MATI - Budiman, Daniel Satria; Sudjiarto, Tatok; Hasiholan, Andree Washington (Fakultas Hukum Universitas Kristen Indonesia, 2025)
The case involving Teddy Minahasa, former East Java Regional Police Chief, attracted public attention because of the death penalty charges against him due to his involvement in drug trafficking. Even though he was charged with the death penalty, in the end the panel of judges decided to sentence him to life imprisonment. This research aims to analyze the legal dynamics that occurred in this case, including the legal considerations that influenced the judge's decision to reduce the sentence from the death penalty to life imprisonment. The approach used in this research is a normative juridical method, which focuses on analysis of court decisions and applicable laws, especially in cases of narcotics crimes involving state officials. It is hoped that the findings from this research will provide insight into the principles of justice in the Indonesian criminal justice system and how judges consider when imposing heavy sentences on perpetrators who have important positions in society.